IMPACTS OF OIL PRICES ON STOCK MARKET INDEXES: NORDIC EVIDENCE - Soininen, Risto (My University, 2018)
The current study was designed to investigate the impact of oil prices on the stock index in the Nordic markets. To complete the study, Brent crude oil price and OMX Nordic 40 Index were used as variables representing the global oil price and Nordic stock market index respectively. The OMX Nordic 40 Index was used as a variable representing the entire Nordic stock markets. The main method of analyzing the data was the Vector Autoregressive (VAR) Model. However, before modeling the data using vector autoregressive, a preliminary analysis was conducted to determine the correlation of the variation as well as seasonality (presence of unit roots) and cointegration. The Spearman rank correlation indicated that variables Brent crude and OMX Nordic 40 Index are weakly correlated. Even there is the presence of negative correlation; it is not significant. Also, the ADF test indicated that the variables have seasonal factors and are cointegrated. To complete the VAR modeling, the dataset was first differenced to remove seasonal factors. The VAR Model provided evidence of the positive influence of oil prices on the Nordic stock market index. The nature of influence is positive but less significant. The analysis further indicated that the positive effects on the Nordic stock market subsequently turns negative before gradually leveling off at zero. That is, the stock market index increases and then decrease due to shocks in the oil prices. However, in the long term, the impact of shocks of the oil prices do not last more than four months.
Keywords: Oil prices; VAR Model; Nordic stock markets; OMXN 40 Index; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|